Degrees of Competitive Speculation - Meade, J. E. (Review of Economic Studies, 1949)
Journal Article Degrees of Competitive Speculation Get access J. E. Meade J. E. Meade London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 3, 1949, Pages 159–167, https://doi.org/10.2307/2296275 Published: 01 January 1949